SCENOGRAPHY OF PUBLIC HOLIDAYS AND THEATER IN OUR COUNTRY - Oxundedaev Xojiakbar Maxamadali ugli (American Journals, 2023)
Evaluation of field performances and theatrical public holidays in Uzbekistan , scenography art process, spectacle of the scene art processes, about the scientific and theoretical theory of the interdependence of theater and public holidays analyzed .
Keywords: Public holiday, stage shows, scenography and art decorations, the organization of the theater, the development of theatrical public holidays.